Reduction of Electron-Rich Nitro Heteroarenes; A Comprehensive Review - Vengatesh, Gopal; Nanjan, Pandurangan (Current Organic Chemistry, 2022)
Amino heterocycles are important in drug design due to their unique intrinsic and physicochemical properties. Though these molecules look simple, their selective reduction is challenging because of their rich electron density in the ring. Additionally, reducing nitro groups in heterocycles is crucial in designing different materials. With this in view, several reduction methods have been developed and applied to various heterocyclic compounds. However, there is no dedicated report on these special types of compounds. With careful analysis, the studies are systematically summarized from conventional methods to advance materials based on their catalytic activity, durability, recyclability, and stability. Further, detailed insights are discussed to motivate chemists working in catalysts.
Keywords: PEG